2005
DOI: 10.1007/s00064-005-1152-0
|View full text |Cite
|
Sign up to set email alerts
|

Nichtsteroidale Antirheumatika (NSAR) in der perioperativen Phase in Traumatologie und Orthopädie

Abstract: Nonsteroidal anti-inflammatory drugs (NSAIDs) are invaluable in treating a variety of musculoskeletal conditions. As well as their excellent analgesic potency their anti-inflammatory effects are beneficial in treating posttraumatic and postoperative edema. In addition, NSAIDs inhibit heterotopic bone formation after hip arthroplasty. Animal studies, however, have demonstrated that they cause delayed fracture healing. Although clinical studies have not yet supplied unequivocal evidence of this effect in human s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…In acute pain after fracture or during the postoperative period after fracture fixation, NSAIDs play an important role due to their pronounced analgesic potency, anti-inflammatory effects, and lesser side effects compared to opioids [7, 45]. However, studies comparing opiates and NSAIDs have shown that NSAIDs are at least as effective as opiates with some studies suggesting that NSAIDs can achieve greater reductions in pain scores [4652].…”
Section: Introductionmentioning
confidence: 99%
“…In acute pain after fracture or during the postoperative period after fracture fixation, NSAIDs play an important role due to their pronounced analgesic potency, anti-inflammatory effects, and lesser side effects compared to opioids [7, 45]. However, studies comparing opiates and NSAIDs have shown that NSAIDs are at least as effective as opiates with some studies suggesting that NSAIDs can achieve greater reductions in pain scores [4652].…”
Section: Introductionmentioning
confidence: 99%
“…The literature provides numerous clinical trials which found that an oral HO prophylaxis (indomethacin) can reduce the incidence of large HO formations (Brooker grades 3 and 4) after certain fractures [ 13 ]. It must be taken into account that NSAIDs can lead to delayed fracture healing and non-unions in animals [ 3 , 4 ]. Despite these results, many patients receive NSAIDs for both, postoperative pain and anti-inflammatory (HO prophylactic) treatment after trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the significance of HO prophylaxis in blunt extremity trauma and fracture treatment. Nevertheless, some studies have suggested that NSAIDs, which suppress inflammatory prostaglandins during initial tissue inflammation, could cause delayed fracture healing in animals [ 3 , 4 ]. Large and symptomatic HO formations can only be treated surgically [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Today, the most commonly used drugs for pain relief in these patients are nonsteroidal anti-inflammatory drugs (NSAIDs) such as diclofenac. Diclofenac is an analgesic, anti-inflammatory drug and one of the most efficient inhibitors of prostaglandins which is used in treatment of rheumatic diseases ( 7 , 8 ). Diclofenac could lead to headache, dizziness, rash, edema, and kidney and liver damage.…”
Section: Introductionmentioning
confidence: 99%